Considerations for Use of Dental Photography and Electronic Media in Dental Education and Clinical Practice. Issue 4 (1st April 2015) - Stieber, Jane C.; Nelson, Travis; Huebner, Colleen E.
Abstract : Photography and electronic media are indispensable tools for dental education and clinical practice. Although previous research has focused on privacy issues and general strategies to protect patient privacy when sharing clinical photographs for educational purposes, there are no published recommendations for developing a functional, privacy‐compliant institutional framework for the capture, storage, transfer, and use of clinical photographs and other electronic media. The aims of this study were to research patient rights relating to electronic media and propose a framework for the use of patient media in education and clinical care. After a review of the relevant literature and consultation with the University of Washington's director of privacy and compliance and assistant attorney general, the researchers developed a privacy‐compliant framework to ensure appropriate capture, storage, transfer, and use of clinical photography and electronic media. A four‐part framework was created to guide the use of patient media that reflects considerations of patient autonomy and privacy, informed consent, capture and storage of media, and its transfer, use, and display. The best practices proposed for capture, storage, transfer, and use of clinical photographs and electronic media adhere to the health care code of ethics (based on patient autonomy, nonmaleficence, beneficence, justice, and veracity), which is most effectively upheld by a practical framework designed to protect patients and limit institutional liability. Educators have the opportunity and duty to convey these principles to students who will become the next generation of dentists, researchers, and educators.